Contribution of CYP2E1 polymorphism to aging in the mechanical workshop workers. (May 2013) - Eshkoor, Sima Ataollahi; Ismail, Patimah; Rahman, Sabariah Abd.; Adon, Mohd Yusoff; Devan, R. Vasu
Abstract Aging is attributed to both genetic and environmental factors. Occupational exposure is one of the environmental factors with potential genotoxic effects. Researchers try to determine factors involved in genetic damages at hazards exposure that could accelerate aging. Cytochrome P450 2E1 (CYP2E1) gene contributes in activation and detoxification of the environmental hazards. This polymorphism plays an important role in susceptibility of inter-individuals to DNA damage at the occupational exposure. The current study evaluated the possible influence of this gene polymorphism in aging by genomic damages through the biomarkers alterations of micronuclei (MN), comet tail length and telomere length shortening at the exposure. In this study, buccal cells were collected from the oral cavity of exposed workers and non-exposed controls. The CYP2E1 genotypes were detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The wild genotype significantly affected MN frequency (p = 0.007) and relative telomere length (p = 0.047) in the older group of workers. It was concluded that the interaction of gene polymorphism and exposure enhances DNA damage and accelerates aging consequently.